Prevalence of human herpesviruses in biliary fluid and their association with biliary complications after liver transplantation - Rauber, Conrad; Bartelheimer, Katja; Rupp, Christian; Schnitzler, Paul; Schemmer, Peter; Sauer, Peter; Weiss, Karl Heinz; Gotthardt, Daniel (BMC gastroenterology, 2019)
Beta-herpesviruses are common opportunistic pathogens that cause morbidity after liver transplantation (LT).